IMPLEMENTASI STRATEGI PEMBELAJARAN PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW DENGAN BANTUAN SOFTWARE MURAL TERHADAP DAYA RETENSI MATEMATIS - Hidayat, Amam Taufiq; Setiawaty, Sri; Fadhilah, Nur (Jurnal Pendidikan Matematika Malikussaleh, 2025)
This study aims to determine the effect of the PQ4R strategy assisted by Mural software on students' mathematical retention. The research was motivated by the low retention ability of Grade X students at SMA Negeri 1 Kuta Makmur, as indicated by AKM results and preliminary retention questionnaires. The study employed a quantitative approach using a quasi-experimental design with a posttest-only control group. The research subjects consisted of class X-1 as the experimental group and class X-2 as the control group, selected through purposive sampling. The data collection instrument was a Likert-scale questionnaire validated by experts. Data analysis techniques included descriptive statistics, normality test, homogeneity test, and independent t-test. The analysis results showed a significant difference in retention scores between the experimental and control groups, with a significance value of 0.000 < 0.05. These findings indicate that the PQ4R strategy assisted by Mural software has a positive effect on improving students' mathematical retention. This strategy can serve as an effective alternative in learning to enhance students' understanding and long-term memory of lesson material.